ANALISIS KEMAMPUAN PENALARAN MATEMATIS DALAM MENYELESAIKAN SOAL LITERASI MATEMATIKA DITINJAU DARI GAYA KOGNITIF SISWA - Sumardi Sumardi; Indah Amalia (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this research is to describe the mathematical reasoning ability possessed by students have to solve mathematical literacy problems in a cognitive style. This research is a qualitative research with a descriptive research design. The data collection techniques used are written tests and interviews. The validity of the data used is technical triangulation. Data analysis in this study is to reduce data, present data, and draw a conclusion. The instruments involved are the GEFT test to categorize students' cognitive styles that will be used in determining research subjects, a written test with mathematical literacy questions for SPLDV material and interview guidelines. The subjects used are 4 students in the field dependent and the field independent cognitive style. The results of this study indicate that FD students are less likely to make assumptions, formulate and provide reasons for solutions. But in terms of manipulating mathematics able to do well. In addition, in drawing conclusions and checking the validity of FD students, they were unable to do so. Meanwhile, FI students are able to make conjectures, manipulate mathematically, draw conclusions from statements and check the validity of an argument. However, in terms of drawing conclusions, compiling and giving reasons for solutions, FI students are less able to do so. So it can be concluded that the mathematical reasoning ability of FD students is lower than that of FI students.